Occurrence of virulence genes in multidrug-resistant Escherichia coli isolates from humans, animals, and the environment: One health perspective - Edwin M. James; Zuhura I. Kimera; Fauster X. Mgaya; Elieshiupendo M. Niccodem; Joely Ezekiely Efraim; Mecky I. Matee; Erasto V. Mbugi (PLoS ONE, 2025)
Escherichia coli is one of the critical One Health pathogens due to its vast array of virulence and antimicrobial resistance genes. This study used multiplex PCR to determine the occurrence of virulence genes bfp, ompA, traT, eaeA, and stx1 among 50 multidrug-resistant (MDR) E. coli isolates from humans (n = 15), animals (n = 29), and the environment (n = 6) in Dar es Salaam, Tanzania. Their association with antimicrobial-resistant genes (ARGs) was determined using Principal Component Analysis (PCA). All 50/50 (100%) MDR E. coli isolates carried at least one virulence gene, with 19/50 (38%) carrying four genes, bfp + traT + eaeA + ompA. The findings showed a high occurrence of virulence genes bfp (82%), traT (82%), eaeA (78%), and ompA (72%); the study detected no stx1 in any of the isolates. In humans, the most detected virulence genes were bfp and traT 14/15 (93.3%); for poultry, it was eaeA 13/14 (92.9%); for pigs, was bfp and traT 13/15 (86.7%); while for river water, it was eaeA 6/6 (100%). The study observed no significant association between virulence genes and ARGs. PCA results show the genes ompA, traT, eaeA, and bfp contributed to the virulence of the isolates, and blaTEM, blaCTX-M, and qnrs contributed to ARGs. The PCA ellipses show that isolates from pigs had more virulence genes than those isolated from poultry, river water, and humans. The high frequency of numerous virulence genes in MDR E. coli isolates from humans, animals, and the environment indicates that these isolates have a very high potential to cause diseases that are difficult to treat because they are MDR.